Factors Affecting the Innovation of Crop-Livestock Integration System (SITT) Adoption in North Minahasa Regency - Judy Mathilda Tumewu; Zadrak M. Warouw; Eusebius K. M. Endoh (AIBPM Publisher, 2024)
The adoption of beef cattle crop-livestock integration system (SITT) innovations in North Minahasa Regency still faces various obstacles. As a result, beef cattle development tends to experience a decline in population, productivity, and competitiveness. The purpose of the study was to determine the factors influencing farmers' attitudes and adoption of SITT technology innovations for beef cattle in North Minahasa Regency. Mixed-method research was conducted from March to May 2024, where 25 extension agents and cattle farmers were selected purposively. The variables used were farmer characteristics, extension worker performance, nature of innovation, communication channels, attitudes, and farmer adoption of SITT. Data analysis used the Spearman rank method. The study revealed a strong correlation between extension worker performance and the nature of innovation on farmers' attitudes and SITT adoption. In contrast, communication behavior exhibited a negligible impact. These findings underscore the critical role of extension agents in facilitating technology adoption. To maximize the effectiveness of extension programs, efforts should focus on enhancing extension worker capabilities and creating innovative solutions tailored to farmers' needs.